A descriptive study of oral cleft cases managed by the Philippine Band of Mercy from 2001-2005 - Ramirez, Marie Perpetua Socorro A.; Tajonera, Rachelle Dorothy T.; Yumul, Giselle (Adviser).
Although oral clefts are not life threatening, a cleft deformity not only seriously impairs the afflicted individual's function such as speech and eating, but also his ability to develop social skills, and to lead a productive adult life in the community. According to the study conducted by the Oral Cleft Registry, the Philippines has one of the highest rates of oral clefting, with an estimated incidence of one in every 500 live births, Based on a study by the Philippine Birth Defect Registry, a joint project of Department of Health and the US National Institute of Human Genetics, Cleft Lips and Palates rank fifth among the most common birth anomaly. There is lack of published journals available in the Philippines to support this information. Therefore, this study aimed to describe the oral cleft patients managed by The Philippine Band of Mercy from 2001 to 2005. Samples include newly opened cases under the management of The Philippine Band of Mercy and its affiliates with the diagnosis of orofacial clefts from 2001 to 2005 both in-house and missions with the exception of 2001 missions only. Results show that there are more males than females that were treated by the organization. The most common type of cleft treated was Unilateral Cleft Lip. The age range where patients sought treatment was one to seven years of age.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Cleft lip; Cleft palate